Complying with greening practices in the new CAP direct payments: An application on Italian specialized arable farms. (February 2017) - Cortignani, Raffaele; Severini, Simone; Dono, Gabriele
Highlights: Ex-ante Evaluation of Common Agricultural Policy 2014–2020 in Italy. Effects of Greening and First Pillar Reform in Specialized Arable Farms. Environmental implications of agricultural land use and land use change. Abstract: The main novelty of the most recent Common Agricultural Policy reform is the greening, which provides a payment to farmers who respect certain 'agricultural practices beneficial for the climate and the environment'. The greening is part of a framework that includes other changes to the first pillar. In the present study the possible impact of first pillar reform on a Farm Accountancy Data Network (FADN) sample of Italian farms was carried out using a Positive Mathematical Programming model. This model considers the mechanisms of production choices according to compliance with the greening practices, as well as possible administrative penalties or reductions in payments in the case of non-compliance. Results showed that while the impact of the greening practices is limited in terms of land use, there were positive effects on environmental indicators. Coupled payments, along with greening practices, determine a larger impact and are effective in achieving environmental goals. Moreover, the system for reducing green payments and levying administrative penalties in case of non-compliance is effective and ensures compliance with practices in almost all farms.